Pengaruh Media Pembelajaran Dan Motivasi Belajar Terhadap Prestasi Belajar Mata Pelajaran IPS Siswa SMP YPM 6 Tarik Sidoarjo - Nanang Wahyono (Jurnal Penelitian dan Pendidikan IPS, 2019)
Liquit Crystal Display (LCD) is frequently as either computer monitor or notebook. Laptop connected projector can be an interesting learning medium. Display on the screen is wide enough at about 2 x 2 meter, is suitable use to a big groups. The combination between laptop and LCD projector can present massage at learning method based on prepare design. Massage design can be audio, dtill visual, moving visual, audio moving visual; audio with colorfull display the students are interested in learning process. This research use an explanatory research approach. The research population SMP YPM 6 Tarik Kabupaten Sidoarjo, using 64 students samples which meanc that 20% from the whole 314 student. The used sampling method is random sampling proportional technique. The method using the previous data sampling has undergone validaty and reliability test which involve 25 students of SMP YPM 6 Tarik Kabupaten Sidoarjo. Meanwhile, data analysis technique uses double linier regression, with the assistance of SPSS versi 16.00. Base on the result of research done by the writer about the influence of the usage of LCD projector in indicator process and learning motivation towards student subject achievement of SMP YPM 6 Tarik Kabupaten Sidoarjo can be concluded that there is signifivant influence achievement between the usage of LCD projector toward social subject achievement of SMP YPM 6 Tarik Kabupaten Sidoarjo. And also there is a simultaneous significant influence between the usage of LCD projector and the student’s learning motivation toward social subject achievement of SMP YPM 6 Tarik Kabupaten Sidoarjo. Therefore, from this research the writer suggest that the social subject teachers of SMP YPM 6 Tarik Kabupaten Sidoarjo had better use learning medium variously either using LCD projector or improving the student’s spirit in the various efforts to improve the student’s study achievement.